Bladder wall thickness – a method for diagnosing overactive bladder - Wilamowska, Agnieszka; Stachowiak, Grzegorz; Stetkiewicz, Tomasz; Połać, Ireneusz; Makowski, Marcin; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Aim of the study: To assess whether transvaginal ultrasound measurement of bladder wall thickness can be used as a test for overactive bladder in women. Material and methods: 92 women aged 46-74 years old who underwent transvaginal ultrasound and urodynamic investigation were included in the study. Results: Women with stress urinary incontinence had bladder wall thickness less than 4 mm. Patients with overactive bladder had bladder wall thickness greater than 4.2 mm; average 5.14 mm. Conclusions: Transvaginal ultrasound measurement of bladder wall thickness can be used as a test for overactive bladder in women with urinary symptoms.